OPTIMIZING SOFT SKILLS IN CREATIVE COMMUNICATION: THE ANCHORING TECHNIQUE IN SKINCARE ADVERTISING - Hanna Sartika Meliala; Yulies Pristina Simanjuntak; Rita Hartati (ADISAM Publisher, 2025)
Effective communication is crucial in the competitive skincare advertising industry, where brands must engage consumers both emotionally and persuasively. This study explores the role of soft skills in creative communication and examines how the anchoring technique influences consumer perceptions in skincare advertising. Using a qualitative approach, the research analyzes the advertisement “STAY YOU. STAY BOUNCY & FIRM WITH Erika Richardo & NEW! LANEIGE BOUNCY & FIRM SLEEPING MASK” from LANEIGE Indonesia’s YouTube account. The findings highlight the importance of interpersonal communication, storytelling, and emotional intelligence in crafting compelling messages that enhance consumer engagement and brand loyalty. Additionally, the anchoring technique, implemented through key ingredient emphasis, positive associations, and message repetition, effectively shapes consumer perception and decision-making. The study concludes that integrating soft skills with strategic communication techniques significantly enhances advertising effectiveness, offering valuable insights for marketers in the skincare industry. The findings show that verbal metaphors like canvas successfully evoke self-expression and identity, emotional anchors enhance product relevance, and visual cues reinforce the consumer’s perception of efficacy and trust.